Strategy for Shaping the Religious Character of SDIT Students Through the Congregational Fardhu Prayer Program - Anhar Khafid; Rahmat Kamal (Madako Elementary School, 2024)
Education plays a crucial role in shaping the attitudes, mindset, spirituality, and character of students, which in turn benefits both individual development and society as a whole. One of the main goals of education is the formation of character based on religious values, which serves as a foundation for creating a quality generation. This study aims to analyze the efforts made by the school principal in enhancing the moral and religious character of students at SDIT Gondang. This research employs a qualitative approach with a field study method, aiming to explore in depth the formation of students' character through the implementation of congregational obligatory prayers during Dhuhur and Asr, which are an integral part of the full-day school program at SDIT Gondang. The data collected comes from interviews, observations, and documentation involving the principal and students, supported by relevant literature. The results of the study show that the congregational Dhuhur and Asr prayers program is expected to foster better and more religious character in students, which ultimately has a positive impact on their daily lives. The contribution of this research emphasizes the importance of integrating religious values into character education, Especially through the practice of congregational prayer in schools.